2013
DOI: 10.1016/j.jviscsurg.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Management of the perineal wound after abdominoperineal resection

Abstract: Although many options are available for the management of perineal wounds after abdominoperineal resection, ranging from direct closure to flap reconstruction, treatment remains challenging. A better understanding of the aims, drawbacks and progress in perineal wound management after abdominoperineal rectal resection can help the surgeon make better choices for each patient, but it is very difficult to propose a single, optimal, evidence-based procedure for the management of pelvic exenteration. Recent progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 62 publications
0
15
0
4
Order By: Relevance
“…Total abdominal hysterectomy (TAH) with vaginectomy and segmental resection of small bowel due to tumor invasion was performed for synchronous operation in the two cases. Postoperative outcomes demonstrated that days to passage of flatus were 2.3 ± 0.9 day (1-4) and days to first soft diet was 4.7 ± 3.4 day (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The mean hospital day was 11.2 ± 4.7 day (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total abdominal hysterectomy (TAH) with vaginectomy and segmental resection of small bowel due to tumor invasion was performed for synchronous operation in the two cases. Postoperative outcomes demonstrated that days to passage of flatus were 2.3 ± 0.9 day (1-4) and days to first soft diet was 4.7 ± 3.4 day (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The mean hospital day was 11.2 ± 4.7 day (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Perineal wound infection, wound dehiscence, perineal abscess, incisional hernia and perineal sinus were inevitable by its extended resection [13]. Therefore, perineal reconstruction was developed to fill the perineal space by using gluteus maximus flaps, the gracilis flap, the perforator flap or biological mesh [14][15][16][17]. Although extralevator APR had favorable oncologic outcomes, it was uncomfortable for longer operation times and a dependency of plastic surgeons for perineal reconstruction [9].…”
mentioning
confidence: 99%
“…Furthermore, colonic J-pouch CAA is preferred -especially when the residual rectum above the anal sphincter is less than 4 cm -because of lowest leakage rates reported [2,11,39,40]. Furthermore, colonic J-pouch CAA is preferred -especially when the residual rectum above the anal sphincter is less than 4 cm -because of lowest leakage rates reported [2,11,39,40].…”
Section: Bowel Reconstructionmentioning
confidence: 99%
“…Technical modifications and flap evolution have recently contributed to modifying the decision algorithm and simplifying some indications. 1 In 1996, Yii and Niranjan described a range of sensitive fascio-cutaneous flaps that were vascularized by the perforators of the internal pudendal vessels. 2 The most popular version, which is centered on the gluteal fold, was variably called the lotus petal flap because of its shape, 3 the infragluteal skin flap, 4 or the gluteal fold flap.…”
Section: Introductionmentioning
confidence: 99%